Design and fabrication of bioactive coatings to catalytically generate nitric oxide on the surfaces of extracorporeal circuits - Wick, Tracey V., author; Reynolds, Melissa M., advisor; Kipper, Matthew, committee member; Olver, Christine, committee member (Colorado State University. Libraries, 2022)
Blood-contacting medical devices suffer from biofouling caused by proteins, platelets and other cells adhering to the surface which often leads to severe complications and eventual device failure. In particular, extracorporeal membrane oxygenation (ECMO) is a life support treatment that is highly prone to coagulation issues due to a large blood-contacting surface area and turbulent blood flow. The ECMO circuits are constructed from catheters, tubing, and an oxygenator which all come into contact with blood and have several connections that alter the blood flow. The standard therapy to decrease thrombotic complications is to administer a systemic anticoagulant, usually unfractionated heparin. While this reduces clotting, harmful and potentially fatal hemorrhagic complications arise. Researchers have looked to nitric oxide (NO), a common biomolecule produced by the endothelium, as an alternative to locally inhibit clotting. Previous work has shown a reduction in thrombotic activity using NO-releasing substances, but these substances only last for a short period of time. An approach explored herein takes advantage of a catalytic mechanism to generate NO from endogenous NO-donors, S-nitrosothiols (RSNOs). RSNOs have been shown to catalytically generate NO through copper catalysis and in particular, with a copper-based metal-organic framework, H3[(Cu4Cl)3(BTTri)8-(H2O)12]·72H2O where H3BTTri = 1,3,5-tris(1H-1,2,3-triazole-5-yl)benzene] (CuBTTri). Importantly, CuBTTri has been shown to be stable under biological conditions and compatible with human cells; therefore, it is a promising candidate for biomedical applications. This report explores the addition of CuBTTri on the surfaces of ECMO. In Chapter 2, a CuBTTri-doped composite is coated onto the extracorporeal circuitry tubing. The fabrication method to apply CuBTTri to the tubing is reported, and the coating was shown to actively generate NO when exposed to a RSNO and no adverse effects were noted during hemocompatibility testing. In Chapter 3, CuBTTri is immobilized on the surface of an ECMO oxygenator using polydopamine. The morphology of the coating was evaluated and the CuBTTri on the surface of the oxygenator was catalytically active, generating NO when exposed to a RSNO. The incorporation of CuBTTri on the surfaces of these components could improve the hemocompatibility of the device, providing a safer and more effective life support system.